Case report: A giant lung leiomyosarcoma: From an accurate diagnosis to a successful surgery. A rare case and brief literature review - Sicolo, Elisa; Mastromarino, Maria Giovanna; Rabazzi, Giacomo; Bacchin, Diana; Ali, Greta; Aprile, Vittorio; Lucchi, Marco (Frontiers in Surgery, 2022)
Primary pulmonary leiomyosarcomas (PPLs) are incredibly rare tumors, characterized by an often-aggressive clinical behavior. Diagnosis is frequently incidental. Whenever present, symptoms are nonspecific, thus PPLs are usually misdiagnosed as other more common respiratory diseases or lung cancer subtypes. Surgery is the best treatment choice and in the therapeutic strategy, timeliness and radicality are of major importance. We report the case of a huge left PPL, successfully treated with salvage surgery after a careful multidisciplinary preoperative assessment, which permitted a prompt diagnostic path and surgery.